Peroxisome proliferator-activated receptor-alpha gene level differently affects lipid metabolism and inflammation in apolipoprotein E2 knock-in mice - Lalloyer, Fanny (Lippincott Williams & Wilkins, 2011)
OBJECTIVE: Peroxisome Proliferator-Activated Receptorα (PPARα) is a ligand-activated transcription factor which controls lipid metabolism and inflammation. PPARα is activated by fibrates, hypolipidemic drugs used in the treatment of dyslipidemia. Previous studies assessing the influence of PPARα agonists on atherosclerosis in mice yielded conflicting results and the implication of PPARα therein has not been assessed. The human apoE2 knock-in (apoE2-KI) mouse is a model of mixed dyslipidemia, atherosclerosis and non-alcoholic steatohepatitis (NASH). The aim of this study was, using homo- and heterozygous PPARα-deficient mice, to analyze the consequences of quantitative variations of PPARα gene levels and its response to the synthetic PPARα agonist fenofibrate, on NASH and atherosclerosis in apoE2-KI mice. METHODS AND RESULTS: Wildtype (+/+), heterozygous (+/−) and homozygous (−/−) PPARα-deficient mice in the apoE2-KI background were generated and submitted to a western diet supplemented or not with fenofibrate. Western diet-fed PPARα−/− apoE2-KI mice displayed an aggravation of liver steatosis and inflammation compared to PPARα+/+ and PPARα+/− apoE2-KI mice, indicating a role of PPARα in liver protection. Moreover, PPARα expression was required for the fenofibrate-induced protection against NASH. Interestingly, fenofibrate treatment induced a similar response on hepatic lipid metabolism in PPARα+/+ and PPARα+/− apoE2-KI mice, whereas, for a maximal anti-inflammatory response, both alleles of the PPARα gene were required. Surprisingly, atherosclerosis development was not significantly different between PPARα+/+, PPARα+/− and PPARα−/− apoE2-KI mice. However, PPARα gene level determined both the anti-atherosclerotic and vascular anti-inflammatory responses to fenofibrate in a dose-dependent manner. CONCLUSIONS: These results demonstrate a necessary, but quantitatively different role of PPARα in the modulation of liver metabolism, inflammation and atherogenesis.